MTs ENGLISH TEACHERS' PERSPECTIVES ON THE INFLUENCE OF LESSON STUDY TO THEIR ACHIEVEMENT MOTIVATION AND TEACHING - Widayanto Widayanto (IJET (Indonesian Journal of English Teaching), 2016)
This study aims to examine MTs English teachers’ perspectives on the influences of LS training assistance participation had on their achievement motivation and teaching performance in the classroom.  The case study explored teachers’ perspectives of how LS training assistance participation affected their achievement motivation and teaching performance in the classroom. Lesson study is a collaborative method of goal setting, instructional planning, assessing its impact, and reflection and refinement of teaching. The lesson study process, or cycle as it is often called, is a teacher-led, student centered and, ultimately student learning. This study revealed that teachers perceived a positive influence of participating in LS training assistance on both their achievement motivation and teaching performance. Specifically these teachers reported changes in their achievement motivation. They also reported changes in their teaching performance in the way of: 1. Planning Learning Program (lesson plan), 2) Implementing learning activities, 3) Making assessment of learning, 4) Implementing school managerial, 5) Developing content knowledge and skills, and 6) Becoming school curriculum developer.Overall, the findings in this study suggest that a majority of the teachers believed that LS training assistance participation affected their achievement motivation and teaching performance in the classroomand that it was an effective way to continue their professional development.